The role of socio-economic status in depression: results from the COURAGE (aging survey in Europe) - Aislinne Freeman; Stefanos Tyrovolas; Ai Koyanagi; Somnath Chatterji; Matilde Leonardi; Jose Luis Ayuso-Mateos; Beata Tobiasz-Adamczyk; Seppo Koskinen; Christine Rummel-Kluge; Josep Maria Haro (BMC, 2016)
Abstract Background Low socio-economic status (SES) has been found to be associated with a higher prevalence of depression. However, studies that have investigated this association have been limited in their national scope, have analyzed different components of SES separately, and have not used standardized definitions or measurements across populations. The aim of the current study was to evaluate the association between SES and depression across three European countries that represent different regions across Europe, using standardized procedures and measurements and a composite score for SES. Method Nationally-representative data on 10,800 individuals aged ≥18 from the Collaborative Research on Ageing in Europe (COURAGE) survey conducted in Finland, Poland and Spain were analyzed in this cross-sectional study. An adapted version of the Composite International Diagnostic Interview was used to identify the presence of depression, and SES was computed by using the combined scores of the total number of years educated (0-22) and the quintiles of the country-specific income level of the household (1-5). Multivariable logistic regression was used to assess the association between SES and depression. Results Findings reveal a significant association between depression and SES across all countries (p ≤ 0.001). After adjusting for confounders, the odds of depression were significantly decreased for every unit increase in the SES index for Finland, Poland and Spain. Additionally, higher education significantly decreased the odds for depression in each country, but income did not. Conclusion The SES index seems to predict depression symptomatology across European countries. Taking SES into account may be an important factor in the development of depression prevention strategies across Europe.